2006
DOI: 10.1590/s0103-84782006000400031
|View full text |Cite
|
Sign up to set email alerts
|

The color of illumination affects the stress response of jundiá (Rhamdia quelen, Quoy & Gaimard, Heptapteridae)

Abstract: This paper provides the first data about physiological responses to stress in jundiá (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…It has been suggested that coloured light could modify fish stress response (Volpato et al., 2004; Barcellos et al., 2006; Karakatsouli et al., 2008). Melanin‐concentrating hormone is able to stimulate food intake in fish and promote growth (Yamanomea et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that coloured light could modify fish stress response (Volpato et al., 2004; Barcellos et al., 2006; Karakatsouli et al., 2008). Melanin‐concentrating hormone is able to stimulate food intake in fish and promote growth (Yamanomea et al., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The opposite results were obtained by Barcellos et al . (). They showed that cortisol level in blood of Rhamdia quelen fingerlings was increased in blue light, and even more in green light (up to 50.4 ng/mL vs. 30.3 ng/mL in white light).…”
Section: Probable Mechanisms Of the Effect Of Colour On Growth (Stresmentioning
confidence: 97%
“…For example, it was demonstrated that in jundiá (Rhamdia quelen) exposed to blue light, cortisol level following stress was reduced compared to the fish exposed to white light (Barcellos et al, 2006).…”
Section: Discussionmentioning
confidence: 99%